Iron Alloy Powders for Additive Manufacturing

JP2025505438AInactive Publication Date: 2025-02-26ARCELORMITTAL SA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024545165
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-31
Filing Date
2023-01-31
Publication Date
2025-02-26
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025505438000001_ABST
    Figure 2025505438000001_ABST
Patent Text Reader

Abstract

The present invention relates to an iron alloy powder for additive manufacturing, obtained by atomization with a gas made of at least 95% by volume of nitrogen, the alloy containing up to 0.5% by weight of carbon, up to 11.0% by weight of titanium, up to 5% by weight of boron, up to 30% by weight of manganese, up to 15% by weight of aluminum, up to 1.5% by weight of silicon, up to 0.5% by weight of vanadium, up to 2% by weight of copper, up to 2% by weight of niobium, the balance being iron and remaining elements, the powder containing internally occurring nitrides and / or carbonitrides of at least one element selected from the group consisting of titanium, aluminum, boron, vanadium, silicon and niobium, the nitrogen content of such iron alloy powder being above the solubility limit of nitrogen in such alloy at the atomization temperature. The present invention also relates to a method for producing such powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an iron alloy powder for the manufacture of parts, in particular for its use in additive manufacturing. The present invention also relates to a method for the manufacture of an iron alloy powder. [Background technology]

[0002] Iron alloy powders for additive manufacturing are typically produced by an atomization process in which fine metal droplets are obtained by forcing a molten alloy stream through a nozzle and impinging the molten alloy stream against a jet of gas introduced into the stream just before it exits the nozzle. The alloy droplets cool as they fall through the spray tower and form powder particles.

[0003] The cooling rate experienced by such powder particles during the fall is very high due to the small size of the droplets and is not uniform from particle to particle. This can lead to the formation of thermodynamically unstable microstructures with inhomogeneous grain sizes. In some cases, some compounds that should precipitate during solidification are not formed.

[0004] When such powder particles are used to produce ferrous alloy parts by additive manufacturing, the resulting parts may inherit from these inhomogeneities, resulting in inhomogeneous service properties. Summary of the Invention [Problem to be solved by the invention]

[0005] It is therefore an object of the present invention to remedy such drawbacks by providing a powder that can be efficiently used to manufacture parts by additive manufacturing methods while maintaining good usage properties throughout the part. [Means for solving the problem]

[0006] To this end, a first subject of the invention consists of an iron alloy powder for additive manufacturing according to claim 1.

[0007] The iron alloy powder according to the invention may also have any of the features recited in any of claims 2 to 5, considered individually or in combination.

[0008] A second subject of the invention consists of a method for producing an iron alloy according to claim 6.

[0009] A third subject of the invention consists of a metal part manufactured by an additive manufacturing process using the iron alloy powder according to the invention or the iron alloy powder obtainable by the method according to the invention, as recited in claim 7.

[0010] The invention will be better understood on reading the following description, given purely by way of illustration and without any intention of limitation, with reference to the following figures: [Brief description of the drawings]

[0011] [Figure 1] 1 is a graph showing the nitrogen solubility limit in iron and titanium alloys at 1600° C. as a function of titanium content. [Diagram 2] Photographs of Ti(C,N) inoculants within TiB2 precipitates and enlargements of such photographs are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The iron alloy powders for additive manufacturing according to the present invention comprise internally occurring nitrides and / or carbonitrides of at least one element selected from the group consisting of titanium, aluminum, boron, vanadium, silicon and niobium, and the nitrogen content of such iron alloy powders exceeds the solubility limit of nitrogen at the atomization temperature in such alloys.

[0013] In standard ferrous alloy factory processes, the nitrogen content in the alloy cannot exceed its solubility limit in such alloy.

[0014] The nitrogen solubility limit in a given iron alloy depends on the temperature, the nitrogen partial pressure and the alloying elements contained in the alloy. Some alloying elements can increase (Cr, Al, Ti...) or decrease (Si, C, P...) the nitrogen solubility.

[0015] Thermodynamics is well known to predict the effects of temperature, iron alloy composition, atmosphere composition, and pressure on this solubility limit. In particular, unless nitrides and / or carbonitrides are formed, nitrogen solubility follows Siewert's law, which states that the amount of nitrogen in a melt at a constant temperature is inversely proportional to the square root of the partial pressure of nitrogen in contact with the melt.

[0016] Above this solubility limit, some additional nitrogen can be incorporated into the iron alloy if it contains alloying elements capable of forming stable nitrides or carbonitrides by precipitation. The total nitrogen content is then the sum of the nitrogen dissolved in the molten steel and the nitrogen precipitated as nitrides or carbonitrides. The density of the nitrides or carbonitrides is generally lower than that of the molten steel, leading to flotation. The wettability of the nitrides or carbonitrides by the molten steel is generally poor, leading to cluster formation.

[0017] Whatever the composition of the iron alloy, standard steel mill practices prevent reaching a high nitrogen content and / or a good distribution of nitrides or carbonitrides after solidification.

[0018] However, it has now been discovered that certain atomization processes applied to suitable iron alloy powders result in the precipitation of nitrides and / or carbonitrides occurring internally, where the nitrogen content of such iron alloy powders exceeds the solubility limit of nitrogen at the atomization temperature in such alloys, and such nitrides and / or carbonitrides are homogeneously distributed in the powder.

[0019] Nitrogen can be introduced into the ferrous alloy during processing of the molten alloy containing at least one element selected from titanium, aluminum, boron, vanadium, silicon and niobium up to the solubility limit predicted by thermodynamics. However, during the atomization process, a complementary addition of nitrogen can be made by controlling the atomization gas composition to contain at least 95% by volume of nitrogen, by setting the atomization temperature at least 1700°C, and by setting the superheat temperature at least 100°C above the liquidus.

[0020] Without being bound by theory, it appears that precipitation of nitrides and / or carbonitrides comprising at least one element selected from titanium, aluminum, boron, vanadium, silicon and niobium occurs on the surface of the droplets prior to absorption by the droplets, resulting in a fine and homogeneous dispersion of such internally occurring nitrides and / or carbonitrides in the powder particles.

[0021] It has then been observed that such nitrides and / or carbonitrides can modify the solidification mechanism within the droplets and act as inoculants for precipitation.

[0022] The powder particles thus obtained exhibit a more homogeneous microstructure in phases and / or precipitates, resulting in the production of parts exhibiting more uniform service properties.

[0023] The solubility curve of nitrogen in an iron alloy, e.g. iron+titanium, can be plotted as a function of the titanium content that can precipitate to form nitrides and / or carbonitrides, as depicted in Figure 1. This curve embodies the boundary between the zone where nitrogen is completely dissolved in solid solution in the alloy (below the curve) and the zone where precipitation occurs (above the curve).

[0024] In a preferred embodiment, the nitrides and / or carbonitrides formed inside the powder particles are selected from the group consisting of AlN, BN, NbN, Si 3 N 4 , Ti(C,N), TiN, VN and V(C,N).

[0025] In the most preferred embodiment, the nitrides and / or carbonitrides formed inside the powder particles may be selected from NbN, TiN, Ti(C,N), VN and V(C,N).

[0026] The powder can be obtained, for example, by first mixing and melting pure elements and / or iron alloys as raw materials, or the powder can be obtained by melting a pre-alloyed composition.

[0027] Pure elements are usually preferred to avoid having excessive impurities originating from iron alloys, as these impurities may facilitate crystallization. Nevertheless, in the present case, it has been observed that impurities originating from iron alloys are not detrimental to the achievement of the present invention.

[0028] Those skilled in the art know how to mix different iron alloys and pure elements to obtain a target composition.

[0029] The present invention applies to iron alloy compositions containing up to 0.3 or 0.5 weight percent carbon, up to 11.0 or 5.0 or 2.0 weight percent titanium, up to 5 or 3 or 1 weight percent boron, up to 30 or 20 or 1 or 0.5 weight percent manganese, up to 15 or 10 weight percent aluminum, up to 1.5 weight percent silicon, up to 0.5 weight percent vanadium, up to 2 weight percent copper, up to 2 or 1 or 0.5 weight percent niobium, the balance being iron and the remaining elements.

[0030] In a preferred embodiment, the minimum amount of carbon is set at 0.001% by weight. In a preferred embodiment, the minimum amount of aluminum is set at 0.001% by weight. In a preferred embodiment, the minimum amount of titanium is set at 0.001 or 0.1 or 0.5% by weight. In a preferred embodiment, the minimum amount of silicon is set at 0.001% by weight.

[0031] Once the composition is obtained by mixing the pure elements and / or iron alloys in the appropriate proportions, it is heated to a temperature at least 100°C above its liquidus temperature and maintained at this temperature to melt all the raw materials and homogenize the melt. The temperature of the melt must be above 1700°C, preferably above 1750°C. Thanks to this overheating and the specific atomization temperature, the viscosity of the molten composition is reduced, which helps to obtain a powder with good properties. Nevertheless, since the surface tension increases with temperature, it is preferable not to heat the composition to a temperature more than 450°C above its liquidus temperature.

[0032] Preferably, the composition is heated to a temperature of at least 100° C. or even better 200° C. above its liquidus temperature. More preferably, the composition is heated to a temperature of 300-400° C. above its liquidus temperature.

[0033] The molten composition is then atomized into fine alloy droplets by forcing the molten alloy stream through an orifice, or nozzle, under moderate pressure and by impinging it with a jet of gas (gas atomization) or water (water atomization). In the case of gas atomization, gas is introduced into the metal stream just before it exits the nozzle and serves to create turbulence as the entrained gas expands (due to heating) and exits into a large collection volume, the atomization tower. The latter is filled with gas to promote further turbulence of the molten metal jet. The alloy droplets cool during their fall in the atomization tower. Gas atomization is preferred as it favors the production of powder particles with a high degree of roundness and a small number of satellites.

[0034] The atomizing gas contains at least 95% by volume of nitrogen and optionally up to 5% by volume of an inert gas, such as argon. Argon increases the melt viscosity more slowly than other gases, such as helium, which promotes the formation of smaller particle sizes. Depending on the amount of nitrides and / or carbonitrides introduced into the powder, the proportion of nitrogen can be increased up to 100% by volume.

[0035] The gas pressure is important as it directly influences the particle size distribution and microstructure of the powder. In particular, the higher the pressure, the higher the cooling rate. Therefore, the gas pressure is usually set between 10 and 30 bar to optimize the particle size distribution and favor the formation of micro / nanocrystalline phases. Preferably, the gas pressure is set between 14 and 26 bar to promote the formation of particles whose size is most compatible with additive manufacturing techniques.

[0036] The nozzle diameter directly affects the flow rate of the molten alloy and therefore the grain size distribution and the cooling rate. The maximum nozzle diameter is usually limited to 4 mm to limit the increase in the average grain size and the decrease in the cooling rate. The nozzle diameter is preferably 2-3 mm to more precisely control the grain size distribution and favor the formation of a specific microstructure.

[0037] The gas to metal ratio, defined as the ratio between gas flow rate (Kg / hr) and metal flow rate (Kg / hr), is preferably maintained between 1.5 and 7, more preferably between 3 and 4. This helps in controlling the cooling rate and thus further promotes the formation of specific microstructures.

[0038] According to one variant of the invention, in the case of moisture absorption, the alloy powder obtained by atomization is dried in order to further improve its flowability. Drying is preferably carried out at 100° C. in a vacuum chamber.

[0039] The alloy powder obtained by atomization can be used as is or can be sieved to retain a particle size better suited to the additive manufacturing technique to be used later. For example, for additive manufacturing by powder bed fusion, the range of 20-63 μm is preferred. For additive manufacturing by laser metal deposition or direct metal deposition, the range of 45-150 μm is preferred.

[0040] Parts made from the metal powder according to the invention can be obtained by additive manufacturing techniques such as laser powder bed fusion (LPBF), direct metal laser sintering (DMLS), electron beam melting (EBM), selective heat sintering (SHS), selective laser sintering (SLS), laser metal deposition (LMD), direct metal deposition (DMD), direct metal laser melting (DMLM), direct metal printing (DMP), laser cladding (LC), binder jetting (BJ), etc., and coatings made with the metal powder according to the invention can also be obtained by manufacturing techniques such as cold spray, hot spray, high velocity oxy-fuel, etc. EXAMPLES

[0041] The following examples and tests presented below should be considered non-limiting in nature and for illustrative purposes only, as they illustrate the advantageous features of the present invention, the importance of the parameters selected by the inventors after extensive experimentation, and further establish the properties that can be achieved with the alloy powders according to the present invention.

[0042] The alloy compositions according to Table 1 were obtained by first mixing and melting the iron alloys and pure elements in the appropriate proportions or by melting pre-alloyed compositions. The compositions of the additive elements expressed in weight percent are summarized in Table 1.

[0043] [Table 1]

[0044] These alloy compositions were heated and then gas atomized under the process conditions summarized in Table 2.

[0045] For all trials, the common input parameters of the nebulizer BluePower AU3000 were:

[0046] [Table 2]

[0047] [Table 3]

[0048] The obtained alloy powders were then dried under vacuum at 100 °C for 0.5-1 days and sieved to separate them according to their size. Fraction F1 is made from particles having a size less than 20 μm. Fraction F2 is made from particles having a size between 20 and 63 μm. Fraction F3 is made from particles having a size greater than 63 to 160 μm. Fraction F4 is made from particles having a size greater than 160 μm. The fractions marked F3-4 are made from particles having a size greater than 63 μm.

[0049] Table 3-Characterization of powder of fraction F2 N content is measured by standard Leco gas analyzer method. Nitrogen solubility at spray temperature is calculated based on thermodynamic calculations. Nitride and carbonitride properties are predicted based on thermodynamic calculations. Nitride and carbonitride size is measured by scanning electron microscopy and is less than 0.5 μm for all trials.

[0050] FeTiB 2 About Fe 2 The presence of B was determined by classical metallographic methods based on polishing and etching. The weight percentages of Ti and B are measured by ICP-photoelectron spectroscopy. TiB 2 The volume percentage of is calculated based on material balance or by classical metallographic image analysis (threshold method).

[0051] [Table 4]

[0052] Nitride or carbonitride precipitation can be used to inoculate the microstructure during solidification or solid-state phase transformation. 2As can be seen in Figure 2, which shows a photo of the powder, the carbonitrides that appear as white areas are usually TiB2 as an inoculant. 2 (appears as a dark area).

[0053] For several other grades with various types of composition, precipitation of different compounds was observed and the nitrogen content was measured, which was above the solubility limit as shown in the table below.

[0054] [Table 5]

[0055] Table 4 - Powder characterization of other fractions Some further characterization was carried out on fractions F1, F3 and / or F4 of some runs.

[0056] [Table 6]

[0057] It can be observed that after atomization in a nitrogen atmosphere, the nitrogen content of the powder is stable regardless of the powder size and solidification rate. No effect of the powder particle size distribution and the associated solidification rate on the nitrogen content of the powder is observed. Nitrogen precipitates inside the particle powder and its content is independent of the specific surface area of ​​the powder.

Claims

1. 1. An iron alloy powder for additive manufacturing, obtained by atomization with a gas made up of at least 95% by volume of nitrogen, the alloy comprising up to 0.5% by weight of carbon, up to 11.0% by weight of titanium, up to 5% by weight of boron, up to 30% by weight of manganese, up to 15% by weight of aluminum, up to 1.5% by weight of silicon, up to 0.5% by weight of vanadium, up to 2% by weight of copper, up to 2% by weight of niobium, the balance being iron and remaining elements, the powder comprising internally occurring nitrides and / or carbonitrides of at least one element selected from the group consisting of titanium, aluminum, boron, vanadium, silicon and niobium, the nitrogen content of such iron alloy powder being above the solubility limit of nitrogen in such alloy at the atomization temperature.

2. 2. The iron alloy powder of claim 1, wherein the average size of such nitrides and / or carbonitrides is less than 0.5 μm.

3. 3. The iron alloy powder of claim 1 or 2, wherein the internally occurring nitrides and / or carbonitrides are included in the precipitate as inoculants.

4. The nitrides and / or carbonitrides distributed in the powder particles are selected from the group consisting of AlN, B(C,N), Nb(C,N), Si 3 N 4 4. The iron alloy powder according to claim 1, wherein the iron alloy powder can be selected from TiN, Ti(C,N), VN and V(C,N).

5. 5. The iron alloy powder of claim 4, wherein the nitride or carbonitride is TiN or Ti(C,N).

6. A method for producing an iron alloy powder for additive manufacturing according to claims 1 to 5, comprising the steps of: - melting an elemental and / or metallic alloy comprising at least one element selected from the group consisting of titanium, aluminum, boron, vanadium, silicon and niobium at a temperature at least 100°C above its liquidus temperature and above 1700°C to obtain a molten composition; - atomizing said molten composition through a nozzle with a gas made up of at least 95% by volume of nitrogen and optionally up to 5% by volume of an inert gas; The method includes:

7. An iron alloy part manufactured by an additive manufacturing process using the iron alloy powder according to claims 1 to 5 or the iron alloy powder obtained by the method according to claim 6.

Citation Information

Patent Citations

  • Process for the additive manufacturing of maraging steels

    WO2021123894A1

  • Metal powder for additive manufacturing

    WO2021124069A1